Esophageal perforation after anterior cervical surgery: a review of the literature for over half a century with a demonstrative case and a proposed novel algorithm - HARMAN, FERHAT (SPRINGER, 2016)
To review relevant data for the management of esophageal perforation after anterior cervical surgery. A case of delayed esophageal perforation after anterior cervical surgery has been presented and the relevant literature between 1958 and 2014 was reviewed. A total of 57 papers regarding esophageal perforation following anterior cervical surgery were found and utilized in this review. The treatment options for esophageal perforation after anterior cervical surgery were discussed and a novel management algorithm was proposed. Following anterior cervical surgery, patients should be closely followed up in the postoperative period for risk of esophageal perforation. Development of symptoms like dysphagia, pneumonia, fever, odynophagia, hoarseness, weight loss, and breathing difficulty in patients with a history of previous anterior cervical surgery should alert us for a possible esophageal injury. Review of the literature revealed that conservative treatment is advocated for early and small esophageal perforations. Surgical treatment may be considered for large esophageal defects.
Keywords: Algorithms; Esophageal perforation; Anterior cervical surgery; Abscess; Spinal fusion; DELAYED PHARYNGOESOPHAGEAL PERFORATION; STERNOCLEIDOMASTOID MUSCLE FLAP; PECTORALIS MAJOR FLAP; SPINAL-CORD INJURY; PLATE FIXATION; GASTROINTESTINAL-TRACT; MANAGEMENT; SCREW; REPAIR; FUSION